Empagliflozin-A New Chance for Patients with Chronic Heart Failure - Klaudia Kowalska; Justyna Walczak; Joanna Femlak; Ewelina Młynarska; Beata Franczyk; Jacek Rysz (MDPI AG, 2021)
The heart failure (HF) epidemic is one of the challenges that has been faced by the healthcare system worldwide for almost 25 years. With an ageing world population and a fast-paced lifestyle that promotes the development of cardiovascular disease, the number of people suffering from heart failure will continue to rise. To improve the treatment regimen and consequently the prognosis and quality of life of heart failure patients, new therapeutic solutions have been introduced, such as an inclusion of Sodium-glucose co-transporter 2 (SGLT-2) inhibitors in a new treatment regimen as announced by the European Society of Cardiology in August 2021. This article focuses on the SGLT2 inhibitor empagliflozin and its use in patients with heart failure. Empagliflozin is a drug originally intended for the treatment of diabetes due to its glycosuric properties, yet its beneficial effects extend beyond lowering glycemia. The pleiotropic effects of the drug include nephroprotection, improving endothelial function, lowering blood pressure and reducing body weight. In this review we discuss the cardioprotective mechanism of the drug in the context of the benefits of empagliflozin use in patients with chronic cardiac insufficiency. Numerous findings confirm that despite its potential limitations, the use of empagliflozin in HF treatment is advantageous and effective.